Nymphaea colorata, another basal angiosperm species with bidirectional cytokinesis in microsporogenesis. (3rd June 2021) - Wu, Hong; Hu, Mingli; Yang, Ming
ABSTRACT: Comparing cellular features in microsporogenesis across taxa may yield important clues to evolution of meiosis in plants. We previously provided evidence that bidirectional cytokinesis occurs in M. denudata and suggested that the same may also occur in P. trimera based on a published report. Both M. denudata and P. trimera are basal angiosperm species that belong to the order of Magnoliales. For comparison, only unidirectional cytokinesis, either centripetal or centrifugal cytokinesis, has been found in microsporogenesis in eudicots and monocots. These observations raise the possibility that bidirectional cytokinesis is a common feature of microsporogenesis in basal angiosperms but not in eudicots and monocots. In this report, we provide evidence that bidirectional cytokinesis also occurs in another basal angiosperm species, Nymphaea colorata . The new findings, together with the previous findings, indicate that bidirectional cytokinesis is a prominent feature of microsporogenesis in at least some basal angiosperm species, and it occurs independently of cytokinesis types with respect to the timing of cytokinesis and tetrad configurations.